2016
DOI: 10.5430/jha.v5n3p76
|View full text |Cite
|
Sign up to set email alerts
|

Physician awareness of patient cardiac telemetry monitoring

Abstract: Overuse of cardiac telemetry monitoring in the inpatient setting is widespread, contributes to alarm fatigue, and is costly for health systems. We sought to quantify the rates of provider unawareness of ongoing telemetry use and to quantify the rate of appropriate monitoring compared to American Heart Association (AHA) guidelines using a survey design. Inpatient medical providers were questioned about the presence of telemetry for each of their patients. In the 870 inquiries, 47% of patients were receiving tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Guidelines for in-hospital cardiac monitoring have been published by the American College of Cardiology [ 11 ]. However, cardiac telemetry continues to be overused due to non-adherence to the guidelines by physicians or due to unawareness of telemetry continuation days [ 6 - 7 , 10 ]. The number of days on telemetry is a clear component in the increment of hospital expenses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guidelines for in-hospital cardiac monitoring have been published by the American College of Cardiology [ 11 ]. However, cardiac telemetry continues to be overused due to non-adherence to the guidelines by physicians or due to unawareness of telemetry continuation days [ 6 - 7 , 10 ]. The number of days on telemetry is a clear component in the increment of hospital expenses.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2009, a day’s cost of telemetric monitoring was at least $1,400 per patient. In some cases, patients are kept on telemetry longer than indicated because providers are unaware of its ongoing use [ 6 - 7 ]. Several strategies have been studied to reduce the overuse of cardiac telemetry [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2016 study by Sharma et al found that 47% of patients reviewed were monitored on telemetry. Of these patients, providers were only aware they were being monitored 74% of the time and only 58% of providers were able to provide guideline-appropriate indications for monitoring [7]. In an attempt to curb inappropriate utilization, the American Heart Association (AHA) and American College of Cardiology (ACC) updated their recommendations for continuous telemetry monitoring in 2017 [8].…”
Section: Introductionmentioning
confidence: 99%